Construct intercorrelations for children's early literacy skills - Juppri Bacotang; Adibah Abdul Latif; Nurfarhana Diana Mohd Nor; Siti Farhana Md. Yasin; Connie Shin @ Connie Cassy Ompok; Nur Suhaidah Sukor; Jusiah Idang (Universiti Pendidikan Sultan Idris, 2022)
This article explains about the construct correlation of early literacy skills for children aged 3+ to 4+. The researchers used a survey which involved 222 children with 119 children aged 3+, and 103 children aged 4+. The study locations were 12 nurseries or kindergartens within Perak and Selangor. The achievement of children’s early literacy skills was assessed using the Early Literacy Skills Indicator (ELSI) which covered five main constructs, namely language and communication, print awareness, phonological awareness, narrative comprehension, and early writing. The Pearson coefficient correlation was used to determine correlation between each construct of early literacy skills and the items. Findings of the intercorrelation analysis showed that there were very strong, strong and moderate, and significant positive correlations between each construct and the items. This study was able to elucidate items or specific skills for each construct of early literacy skills. Besides, this study could also assist parents and educators to expose comprehensive early literacy skills to children aged 3+ to 4+.